Análise acústica do ditongo [eI] em inglês e em português por falantes bilíngues - Gomes, Maria Lúcia de Castro; Bernardo-Silva, Otávio Augusto (Language and Law / Linguagem e Direito, 2019)
It is said that diphthongs carry potentially useful individualizing information about the speaker and this has been investigated and used in forensic analysis. Also, research projects concerned with bilingualism and differences between L1 and L2 are becoming more and more common contexts for forensic phonetics. These two facts motivated this study into bilingualism and acoustic analysis, specifically into diphthong production. The diphthong [aI] has been the focus of a great deal of research, but the focus of our research was the diphthong [eI], which presents more complexity due to the acoustic proximity of vowel and glide. This article aims at demonstrating the results of acoustic analyses of [eI] in pairs of Portuguese and English words such as lei/lay and leis/lays, as produced by bilingual speakers. The results show that the comparison of acoustic measures, such as duration and formant frequency, can reveal special characteristics of groups of speakers and idiosyncratic features of individual speakers, in both L1 and L2.